1992
DOI: 10.1037/h0080614
|View full text |Cite
|
Sign up to set email alerts
|

Mood and HIV risk behavior among drug-dependent veterans.

Abstract: This study extends prior investigations of risk behaviors for contracting and transmitting the human immunodeficiency virus (HIV) among treatment-seeking drug abusers bv analyzing the relationship between HIV risk behavior and drug use and psychopathology variables The Beck Depression Inventory' the State-Trait Anxiety Inventory and measures of knowledge related to the acquired immunodeficiency svndrome (AIDS) were administered to 170 consecutive admissions to a Veterans Administration drug dependence treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A number of studies with methadone maintenance or other drug treatment patients (Camacho, et al, 1996; Kleinman, et al, 1994; Malow, et al, 1992; Metzger, et al, 1991; Perdue, et al, 2003; Pilowsky, et al, 2011; Woody, et al, 1997), and drug users not in treatment (Johnson, et al, 2003; Johnson, et al, 2002; Simpson, et al, 1993; Strathdee, et al, 1997), including syringe exchange program participants (Kidorf, et al, 2010), have found that symptoms of psychological distress or dysfunction, particularly symptoms of depression, are associated with injection risk behavior, including sharing syringes and other equipment, number of sharing partners, sharing with strangers, and sharing with a person known to be HIV-positive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies with methadone maintenance or other drug treatment patients (Camacho, et al, 1996; Kleinman, et al, 1994; Malow, et al, 1992; Metzger, et al, 1991; Perdue, et al, 2003; Pilowsky, et al, 2011; Woody, et al, 1997), and drug users not in treatment (Johnson, et al, 2003; Johnson, et al, 2002; Simpson, et al, 1993; Strathdee, et al, 1997), including syringe exchange program participants (Kidorf, et al, 2010), have found that symptoms of psychological distress or dysfunction, particularly symptoms of depression, are associated with injection risk behavior, including sharing syringes and other equipment, number of sharing partners, sharing with strangers, and sharing with a person known to be HIV-positive.…”
mentioning
confidence: 99%
“…Young people who inject drugs (PWID) frequently experience mental health problems, including mood, anxiety, and personality disorders, as well as alcohol and other substance use disorders (Brooner, King, Kidorf, Schmidt, & Bigelow, 1997; Callaly, Trauer, Munro, & Whelan, 2001; Kessler, 2004; Kessler et al, 2005; Mackesy-Amiti, Donenberg, & Ouellet, 2012; Mason et al, 1998; Teesson et al, 2005). A number of studies with methadone maintenance or other drug treatment patients (Camacho, Brown, & Simpson, 1996; Kleinman et al, 1994; Malow, Corrigan, Pena, Calkins, & Bannister, 1992; Metzger et al, 1991; Perdue, Hagan, Thiede, & Valleroy, 2003; Pilowsky, Wu, Burchett, Blazer, & Ling, 2011; Woody, Metzger, Navaline, McLellan, & O’Brien, 1997), and drug users not in treatment (Johnson, Brems, Wells, Theno, & Fisher, 2003; Johnson, Yep, Brems, Theno, & Fisher, 2002; Simpson, Knight, & Ray, 1993; Strathdee et al, 1997), including syringe exchange program participants (Kidorf et al, 2010), have found that symptoms of psychological distress or dysfunction, particularly symptoms of depression, are associated with injection risk behavior, including sharing syringes and other equipment, number of sharing partners, sharing with strangers, and sharing with a person known to be HIV-positive.…”
mentioning
confidence: 99%
“…In understanding the motivations for SRB, it is also useful to consider the role of psychopathology and other clinical correlates (Impett et al, 2005). Indeed, there is a strong and consistent link between SRB and three forms of mental illness including depression (e.g., Hogben et al, 2001;Hutton et al, 2004;Kalichman, 1999;Malow, Corrigan, Pena, Calkins, & Bannister, 1992;Murphy et al, 2001;Simpson, Knight, & Ray, 1993), borderline personality disorder (BPD; Chen, Brown, Lo, & Linehan, 2007;Frankenburg & Zanarini, 2004;Hull, Clarkin, & Yeomans, 1993), and posttraumatic stress disorder (PTSD;Degenhardt & Copeland, 2006;Farley & Barkan, 1998;Roberts, Wechsberg, Zule, & Burroughs, 2003). Further, there is a commonly found relationship between SRB and childhood trauma (Merrill, Guimond, Thomsen, & Milner, 2003).…”
mentioning
confidence: 99%
“…Several features associated with depression, such as dysphoric mood, negativistic thinking, decreased self-efficacy, negative self-perception, and low assertiveness have been linked to increased levels of risky sexual behaviors and thus at increased risk for contracting HIV (Gold & Skinner, 1992;Morris & Reilly, 1987). The higher prevalence of substance abuse among depressed persons further increases their risk of becoming infected with HIV due to the decreased cognitive impairment and increased risk behavior (e.g., needle sharing, sex trade) associated with substance use (Joe, Knezek, Watson, & Simpson, 1991;Malow et al, 1992;Marks et al, 1998;Waddell, 1992). It has also been suggested that the association with risk behavior may lie in the altered self-regulatory processes of those with negative affect states (Crepaz & Marks, 2001;Gold & Skinner, 1992;Morris & Reilly, 1987).…”
mentioning
confidence: 99%